THE EFFECT OF GOOD GOVERNANCE IMPLEMENTATION, GOVERNMENT ACCOUNTING STANDARDS, EFFECTIVENESS OF INTERNAL CONTROL SYSTEM AND HUMAN RESOURCE QUALITY ON THE QUALITY OF REGIONAL TASK FORCE FINANCIAL STATEMENTS - Agus Siahaya; Sally Paulina Sandanafu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this research is examine the effect of implementation of Good Governance, Government Accounting Standards, Effectiveness of Internal Control System and Quality of Human Resources to the Quality of Financial Statements in the local municipality and regency (SKPD) Ambon, Maluku province. The population are 90 SKPD in the province of Maluku and each sample represented by one respondent. This research using quantitative approach, and data collection was done directly by using the questionnaire. Data were analyzed using Partial Least Square Equational Structural Models (PLS-SEM) with SmartPLS program. The results showed that the implementation of good governance, Government Accounting Standards, Quality of Human Resources positive significantly affect the Quality of Financial Statements Municipal area and the regency of Ambon, Maluku. Effectiveness of Internal Control System is not significant to the Quality of the Financial Statements in the local municipality and regency Ambon, Maluku.